The conceptual metaphors of memory: Cases of interdomanial nomadism from computer science to quantum computing - Charlène Meyers (Lexis: Journal in English Lexicology)
Conceptual metaphors, which help conceptualizing one concept in terms of another (Lakoff & Johnson [1980]), often migrate from a source scientific domain onto another. This article aims at describing the “interdomanial nomadism” (Rossi [2015]) of the conceptual metaphors associated with memory from computer science to quantum computing. One corpus of 35 texts about quantum computing was compiled from the Scientific American. This corpus is made of all the texts ever published in the magazine which contain the keywords “quantum computing” or “quantum computer(s)”. Another corpus of 15 texts about computer memory was compiled from the same magazine. The search for these texts was refined by looking for the keyword “computer memory” and excluding the keyword “quantum”. Our analysis relies on the extraction of terms related to memory in both corpora (more specifically on the terms that the corpora have in common) and on the identification of their metaphoricity to investigate any potential interdomanial shifts. First, we extracted the keywords from both corpora in Sketch Engine (Kilgarriff et al. [2014]). This extraction gave us a general idea of the conceptual metaphors of memory in both computer science and quantum computing. Then, we observed, through the means of similarity analysis, the words which co-occur the most with the word “memory” in a close context. This observation enabled us to have a further look at potential metaphorical expressions associated with memory. The MIPVU method (Metaphor Identification Procedure Vrije Universiteit Amsterdam) developed by Steen et al. [2010] was selected to identify metaphorical items in the corpora. The analysis of the keywords resulted in the identification of 9 conceptual metaphors used to describe memory, among which 4 are common to both corpora, providing first evidence of metaphorical nomadism of memory from computer science to quantum computing. Additionally, 5 types of nomadic patterns were identified based on the examples from the corpora, providing better insight into metaphor interdomanial nomadism.